Asuhan Kebidanan Komprehensif pada Ny. T, Umur 22 Tahun, G1P0A0 di Desa Sukorejo, Kecamatan Kesesi, Kabupaten Pekalongan - Kamini; Hapsari Windayanti (Universitas Ngudi Waluyo, 2025)
Maternal and neonatal mortality remain major challenges in Indonesia's healthcare system. One effective strategy to reduce maternal mortality rate (MMR) and infant mortality rate (IMR) is the implementation of Continuity of Care (CoC), a comprehensive and continuous midwifery care approach from pregnancy through childbirth, postpartum, newborn care, and family planning. This case study aims to describe the implementation of comprehensive midwifery care for Mrs. T, a 22-year-old primigravida (G1P0A0), in Sukorejo Village, Kesesi District, Pekalongan Regency. This descriptive research employed a case study design and was carried out using the seven-step Varney midwifery management process, documented using the SOAP format. Antenatal care was provided at 38 weeks of gestation, during which the mother and fetus were found to be in physiological condition with no complications. Counseling focused on nutrition, adequate rest, birth preparedness, and recognizing early signs of labor. During labor, comprehensive care was provided through all four stages of delivery. Labor progressed spontaneously, and the baby was delivered in good condition with a birth weight of 3,450 grams. Postpartum care was carried out in three visits, showing no signs of complications and indicating a normal recovery. The mother was counseled about postpartum nutrition, breastfeeding, and newborn care. Newborn care included physical examination, administration of vitamin K, immunization with Hepatitis B (Hb 0), and education on thermal protection and exclusive breastfeeding. In the family planning phase, the mother received counseling on various contraceptive methods, including their benefits and possible side effects. She chose a long-acting reversible contraceptive (LARC), specifically an implant. The decision was made with informed consent, and she expressed readiness to adhere to the recommended method. This case study found no gap between theoretical knowledge and clinical practice. The care provided was aligned with national midwifery service standards and demonstrated the effectiveness of CoC in improving maternal and neonatal health outcomes. Furthermore, it highlights the importance of integrating CoC into midwifery education to ensure students gain practical skills and experience in providing comprehensive care. Abstrak Angka Kematian Ibu (AKI) dan Angka Kematian Bayi (AKB) masih menjadi tantangan utama dalam pelayanan kesehatan maternal di Indonesia. Salah satu upaya untuk menurunkan angka tersebut adalah melalui pendekatan Continuity of Care (CoC), yaitu pemberian asuhan kebidanan secara menyeluruh dan berkesinambungan mulai dari masa kehamilan, persalinan, nifas, bayi baru lahir hingga pelayanan keluarga berencana (KB). Penelitian ini merupakan studi kasus yang bertujuan untuk memberikan gambaran pelaksanaan asuhan kebidanan komprehensif pada Ny. T, usia 22 tahun, G1P0A0, di Desa Sukorejo, Kecamatan Kesesi, Kabupaten Pekalongan. Metode yang digunakan adalah studi deskriptif dengan pendekatan studi kasus, yang dilaksanakan berdasarkan tujuh langkah proses kebidanan Varney dan dicatat dalam format SOAP. Asuhan kehamilan dilakukan pada usia gestasi 38 minggu, menunjukkan kondisi ibu dan janin dalam keadaan fisiologis tanpa keluhan atau risiko yang memerlukan penanganan khusus. Asuhan persalinan diberikan secara menyeluruh dari kala I hingga kala IV, dengan hasil persalinan spontan dan bayi lahir dalam kondisi sehat. Selama masa nifas dilakukan tiga kali kunjungan yang menunjukkan kondisi ibu dalam masa pemulihan yang baik, dan tidak ditemukan komplikasi. Asuhan pada bayi baru lahir meliputi pemeriksaan fisik, pemberian imunisasi hepatitis B (Hb 0), edukasi perawatan bayi, serta dukungan terhadap praktik menyusui eksklusif. Pada fase KB, ibu memilih metode kontrasepsi implan setelah diberikan konseling terkait jenis, manfaat, serta efek samping alat kontrasepsi jangka panjang. Hasil dari studi kasus ini menunjukkan tidak adanya kesenjangan antara teori dan praktik, serta pelaksanaan asuhan kebidanan yang sesuai dengan standar pelayanan kebidanan. Kesimpulan dari studi ini adalah bahwa pendekatan Continuity of Care secara komprehensif dan konsisten dapat mendeteksi dini risiko dan meningkatkan kualitas kesehatan ibu dan bayi. Pendekatan ini juga memberikan pengalaman belajar langsung bagi mahasiswa dalam mengaplikasikan teori ke dalam praktik nyata.